2017
DOI: 10.1515/forj-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in atmospheric depositions in Slovakia

Abstract: The aim of this paper was to analyse temporal changes in chemism of atmospheric deposition in Slovakia. Two kinds of deposition, bulk and throughfall were considered and analysed for the period of 1996-2010. Data acquired from permanent monitoring plots (PMP) of Level II were used for this purpose. These plots were established as a part of the ICP Forests Programme. The changes in the composition of deposition were identified for the spruce and beech plots. The results were compared among three spruce plots, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…Although other studies of alpine grasslands (Evangelista et al, 2016;Gritsch et al, 2016) showed an increase in temperature indicator values, we found such an increase only for certain vegetation 1970s-1980s (Rodhe et al, 1995Hédl et al, 2011) and still receives high deposition of atmospheric nitrogen (Krupová et al, 2018). This is in contrast to some studies that have found impacts of temperature rise on alpine grasslands, especially on high mountain summits (Walther et al, 2005;Pauli et al, 2007;Steinbauer et al, 2018),…”
Section: Limited Evidence Of Changes In the Abiotic Environmentcontrasting
confidence: 98%
See 2 more Smart Citations
“…Although other studies of alpine grasslands (Evangelista et al, 2016;Gritsch et al, 2016) showed an increase in temperature indicator values, we found such an increase only for certain vegetation 1970s-1980s (Rodhe et al, 1995Hédl et al, 2011) and still receives high deposition of atmospheric nitrogen (Krupová et al, 2018). This is in contrast to some studies that have found impacts of temperature rise on alpine grasslands, especially on high mountain summits (Walther et al, 2005;Pauli et al, 2007;Steinbauer et al, 2018),…”
Section: Limited Evidence Of Changes In the Abiotic Environmentcontrasting
confidence: 98%
“…Although other studies of alpine grasslands (Evangelista et al, 2016;Gritsch et al, 2016) 1970s-1980s (Rodhe et al, 1995Hédl et al, 2011) and still receives high deposition of atmospheric nitrogen (Krupová et al, 2018). This is in contrast to some studies that have found impacts of temperature rise on alpine grasslands, especially on high mountain summits (Walther et al, 2005;Pauli et al, 2007;Steinbauer et al, 2018), or suggested impacts of atmospheric nitrogen deposition (Britton et al, 2009;McGovern et al, 2011;Ross et al, 2012).…”
Section: Limited Evidence Of Changes In the Abiotic Environmentmentioning
confidence: 89%
See 1 more Smart Citation
“…The sampled areas in the border region between the Czech Republic, the Slovak Republic, and Austria faced different degrees of anthropogenic SOx and NOx emissions (Krupová et al 2018 ). In particular, the Beskid Mountains in the NE Czech Republic have experienced considerable recent anthropogenic impacts, as they have received significant industrial contamination and acid emissions primarily from the heavy industry in Silesia (Vácha et al 2015 ; Pavlů et al 2015 ; Matys Grygar et al 2023 ).…”
Section: Study Area and Methodsmentioning
confidence: 99%
“…In particular, the Beskid Mountains in the NE Czech Republic have experienced considerable recent anthropogenic impacts, as they have received significant industrial contamination and acid emissions primarily from the heavy industry in Silesia (Vácha et al 2015 ; Pavlů et al 2015 ; Matys Grygar et al 2023 ). Generally, SOx and NOx emissions in the entire NE Czech Republic have been above average during the last decades (Krupová et al 2018 ), and the primary emission source for the Beskid study area was the coke, iron, and steel production in Třinec that was established in 1839 and expanded in the second half of the twentieth century. The emission loads from Třinec peaked in the 1960s (Fig.…”
Section: Study Area and Methodsmentioning
confidence: 99%